2020
DOI: 10.1111/sdi.12942
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of soluble klotho level with uremic cardiomyopathy and ecocardiographic parameters in hemodialysis patients

Abstract: There are studies reporting that soluble kltho (sKlotho) deficiency plays a role in cardiovascular disease in addition to traditional risk factors such as diabetes, hypertension, anemia, smoking, and excessive volume burden. Our aim in this study was to investigate the relationship of sKlotho with uremic cardiomyopathy and echocardiographic parameters in patients receiving hemodialysis treatment. According to the median value, the sKlotho value was divided into two groups as ≥1.24 and <1.24 ng/ml. Ventricular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…Similarly, Nowak et al (2014) found no association between higher sKlotho levels and a lower risk for mortality in 329 MHD patients with sKlotho either as a continuous variable or a categorical variable in multivariable-adjusted analysis after 2.53 years of follow-up ( Nowak et al, 2014 ). Similar inconsistent results were also demonstrated by other recent prospective cohort studies ( Zheng et al, 2018 ; Adamska-Tomaszewska et al, 2020 ; Erkus et al, 2021 ). The inconsistent studies were summarized and the average score was 7 stars, as shown in Table 3 .…”
Section: The Controversy Of Sklotho As a Biomarker In Clinical Nephro...supporting
confidence: 81%
“…Similarly, Nowak et al (2014) found no association between higher sKlotho levels and a lower risk for mortality in 329 MHD patients with sKlotho either as a continuous variable or a categorical variable in multivariable-adjusted analysis after 2.53 years of follow-up ( Nowak et al, 2014 ). Similar inconsistent results were also demonstrated by other recent prospective cohort studies ( Zheng et al, 2018 ; Adamska-Tomaszewska et al, 2020 ; Erkus et al, 2021 ). The inconsistent studies were summarized and the average score was 7 stars, as shown in Table 3 .…”
Section: The Controversy Of Sklotho As a Biomarker In Clinical Nephro...supporting
confidence: 81%
“…Furthermore, the decline of serum sKlotho in CKD has also been associated with carotid intima-media thickening [69], atherosclerosis [70,71], arterial stiffness [72] and hypertension [73]. However, this remains a controversial topic, as certain studies have not identified such associations in CKD [64,[74][75][76][77]. Unfortunately, studies with urinary sKlotho are scarce, so the possible value of urinary sKlotho as a marker or predictor of cardiovascular abnormalities among the CKD-MBD setting has limitations.…”
Section: Soluble Klotho As a Biomarker Of Cardiovascular And Bone Alt...mentioning
confidence: 99%